KARAKTERISTIK BIKA AMBON TAPIOKA DENGAN PUREE UBI JALAR UNGU - WASTRIANI BR TARIGAN; FAIZAH HAMZAH; RAHMAYUNI RAHMAYUNI (Universitas Riau, 2019)
Bika ambon is one of the typical cakes from Indonesian. The purpose of this research was to obtain the bestratio of tapioca and purple sweet potato puree on the characteristics of bika ambon. This research used aCompletely Randomized Design (CRD) with 5 treatments and 3 replications. The treatments in this researchwer; without the addition of purple sweet potato (P0), ratio of tapioca and purple sweet potato puree 80:20(P1), ratio of tapioca and purple sweet potato puree 60:40 (P2), ratio of tapioca and purple sweet potatopuree 40:60 (P3), and ratio of tapioca and purple sweet potato puree 20:80 (P4). The results show that theratio of tapioca and purple sweet potato puree significantly affected the moisture, fat, protein, crude fiber,antioxidant activity, colour, texture, as well as hedonic test, but not significant to sucrose, flavour, cavity, andtaste. The best formulation of bika ambon was P3 with moisture 38.17%, fat 12.13%, protein 3.83%, sucrose16.53%, crude fiber 1.23%, antioxidant activity 87.42 ppm. Organoleptic scores of P3 were colour score 3.53(purple), aroma score 3.57 (flavored with typical fermentation and typical roast), cavity score of 3.93(hollow) texture score 4.27 (soft), taste score 3.63 (sweet), and overall acceptance score 3.37 (like).